Navigating the Legal Landscape: A Comparative Analysis of Digital Asset Regulation across Global Jurisdictions - Zhaksylykbayeva, Assem; Suleimenova , Saule (Law, State and Telecommunications Review, 2026)
[Purpose] The study analysed the legal frameworks governing digital assets in different jurisdictions. The experience of Kazakhstan, Poland, the USA, Uzbekistan, Kyrgyzstan, Singapore, China and South Korea was addressed. [Methodology/approach/design] The study employed a comparative legal analysis methodology, examining regulatory documents. The investigation methodically examined critical regulatory elements across nations, encompassing licensing, taxation, investor protection, and the prevention of financial crime. Legal papers and court rulings were classified and encoded based on established criteria to facilitate systematic cross-jurisdictional comparisons. Significant focus was placed on the examination of the Kazakh regulatory framework, which integrates an innovative methodology for cryptocurrency mining with conventional financial rules, alongside the Polish experience in executing European directives while accounting for country particularities. [Findings] The study revealed significant differences between Asian and European approaches to regulation, with Central Asian countries showing a tendency to develop a domestic regulatory model that accounts for regional specifics. The results showed significant differences in approaches to licensing, taxation and investor protection between developed and emerging markets. Three dominant regulatory models were identified: the US securities-based approach, the Asian approach with a focus on payment systems, and the European integrated approach. Key differences were observed in the requirements for the safekeeping of digital assets and investor protection measures. The study concluded a need to strengthen international regulatory coordination and develop harmonised standards, especially between the European Union, Central Asia and developed Asian financial centres. An important aspect of the study was the identification of the need to create a unified methodology for assessing the effectiveness of regulatory regimes, which would allow for a more accurate comparative analysis of different jurisdictions. Particular attention was devoted to the analysis of the impact of technological innovations on the development of regulatory approaches, in the context of the introduction of distributed registry systems and smart contracts. The study also highlighted the importance of establishing mechanisms to respond quickly to new challenges in the regulation of digital assets, including cybersecurity and personal data protection. [Practical implications] The findings offer regulators actionable insights for aligning national digital asset frameworks with global standards while accounting for local market specifics, enhancing investor protection and regulatory effectiveness. [Originality/value] This study provides a novel comparative analysis of eight jurisdictions, offering valuable guidance for policymakers and scholars on harmonising digital asset regulation globally.